The ritual killing and burial of animals: European perspectives - Pluskowski, Aleksander (Oxbow Books, 2012)
Introduction : the ritual killing and burial of animals in the past / Aleksander Pluskowski -- Animal 'ritual' killing : from remains to meanings / James Morris -- Ritualisation (or The four fully articulated ungulates of the apocalypse) / Lee Broderick -- Nourishment for the soul, nourishment for the body : animal remains in early medieval Pomeranian cemeteries / Andrzej Kuczkowski and Kamil Kajowski -- Spatial aspects of globular amphora culture funeral rites with animal deposits in Poland / Radosław Szczodrowski -- Horse burials as public ritual : Lithuanian perspectives / Mindaugas Bertašius -- Protohistoric animal deposits in the Alps. Considerations regarding a dog, a pig and four human neonates from the rural settlement of Gamsen (Valais, Switzerland) / Nicole Reynaud Savioz -- Late antique and early medieval animal burials in Italy / Frank Salvadori -- Distinct from the everyday and beyond counting calories : animal bones from "ritual spaces" in late Neolithic settlements at Lake Constance and in Upper Suebia / Karlheinz Steppan -- Animal deposits in the late Copper Age settlement of Balatonőszöd-Temetői dűlő, Hungary / Tünde Horváth -- Dealing with deposits in the Dutch River Area : animals in settlement rituals in the Roman period / Maaike Groot -- Sheep foundation burials in Roman Winchester / Mark Maltby -- Early Anglo-Saxon horse culture and funerary ritual (c. AD 450-650) : active mythology in a European context / Chris Fern -- Evolving traditions : horse slaughter as part of Viking burial customs in Iceland / Rúnar Leifsson -- Sacred cows or old beasts? : a taphonomic approach to studying ritual killing with an example from Iron Age Uppåkra, Sweden / Ola Magnell -- Flesh on the bones : animal bodies in Atlantic roundhouses / Jacqui Mulville [and others] -- "Stone dead" : dogs in a medieval sacral space / László Bartosiewicz.